A comprehensive model of disordered eating among aesthetic athletic girls: Exploring the role of body image-related cognitive fusion and perfectionistic self- presentation - Oliveira, Sara (2020)
The incidence of disordered eating among athlete populations is considerably higher thant in the general population. Less well understood is the body image-related emotional processes that might lead to disordered eating attitudes and behaviours, specifically among aesthetic athletic girls. Thus, the aim of the present study was to explore the role that body image-related cognitive fusion plays in disordered eating, and the mediating role of body image-related perfectionist self-presentation on this relationship, in aesthetic athletic girls. This study comprised 142 young female athletes from aesthetic sports, who completed self-report measures. A path analysis was conducted to explore the proposed theoretical model, while controlling for age and zBMI. The path model revealed an excellent fit and explained 71% of the severity of disordered eating. Results showed that body image related cognitive fusion influences disordered eating behaviours, through the mechanism of body image-related perfectionist self-presentation, even when controlling for age and zBMI. Findingssuggested that, in aesthetic athletic girls, the entanglement in body image-related thoughts may be associated with the need to present a perfect body image to others, which may lead to disordered eating attitudes and behaviours, adopted as a means to control weight and body shape. The present study highlights the relevance of body image-related processes in disordered eating and suggests the importance of educational programme that target the development of more adaptive emotion regulation strategies concerning body image in athletes, particularly from aesthetic sports.